PENGARUH LITERASI KEUANGAN DAN PENGENDALIAN DIRI TERHADAP PERILAKU KONSUMTIF MAHASISWA JURUSAN EKONOMI PEMBANGUNAN FAKULTAS EKONOMI UNIVERSITAS NEGERI MALANG ANGKATAN 2013 - Okky Dikria; Sri Umi Mintarti (Universitas Negeri Malang, 2016)
Consumptive behavior is activates that are not based on need but on desire and satisfaction itself. Consumptive behavior comes not from self, but from process certain someone but in private hearts, between lay namely about financial knowledge and self-control in consume. The phenomenon at the State University of Malang showed their consumptive behavior is hapen in student, it can be seen from the student appearance follow the trend of use of mobile phones well as higt price. Behavior such as research feared would disrupt student life hearts because later consumptive behavior of students will continue to take root and can be life & style consumptive. This study uses a population study with proportional random sampling technique with 192 respondent. The collection of data by using questionnaires and test. The method is descriptive quantitative. Analysis of the data used is multiple linier regression analysis. The results of this research showed three results. First, economy literacy negatively affected on consumptive behavior with effective contribution by 19,2%. Second, self-control negatively affected consumer behavior with effective contribution by 4,6%. Third, economy literacy and self-control negatively affected on consumptive behavior with effective contribution by 23,8%.Keywords: financial literacy, self control and consumptive behavior